2021
DOI: 10.1192/j.eurpsy.2021.794
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on young people’s mental health in latvia

Abstract: IntroductionThere is an ongoing debate about the impact on mental health associated with Covid-19 pandemics. Some studies have shown an increase in depressive and anxious symptomatology in general population. It has been noted that young people might be among the highest risk populations due to various enviorenmental and developmental influences.ObjectivesTo estimate the impact of Covid-19 related restrictions on mental health measures among Latvian adolescents and young adults (14-24).MethodsWe conduct a surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The report confirmed that pandemic restrictions had a serious impact on mental health. The obtained data showed that more than 40% of respondents experienced learning difficulties and depression, faced obsessive thoughts, suffered from irritability, and had an increased feeling of loneliness [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…The report confirmed that pandemic restrictions had a serious impact on mental health. The obtained data showed that more than 40% of respondents experienced learning difficulties and depression, faced obsessive thoughts, suffered from irritability, and had an increased feeling of loneliness [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several prior studies among Bangladeshi students have repeatedly noted asignificant mental repercussions specially among university students (Anjum et al, 2019;Cao et al, 2020;Hossain et al, 2020;Konstantinovs & Lapa, 2021). As a result of the suspension of educational activities, together with the disruption of regularity and restricted human interactions, 83% believe that their already existing mental disorders have been aggravated (Konstantinovs & Lapa, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several prior studies among Bangladeshi students have repeatedly noted significant mental repercussions, especially among university students 1,15, 16 . As a result of the suspension of educational activities, together with the disruption of regularity and restricted human interactions, 83% believe that their already existing mental disorders have been aggravated 17 . However, in low-and middle-income countries (LMICs), such as Bangladesh, where few resources are available to combat COVID-19, mental health concerns are more prevalent as a result of this outbreak.…”
Section: Introductionmentioning
confidence: 99%